Partisipasi Masyarakat Dalam Pengembangan Kepariwisataaan Kelurahan Agrowisata Di Kota Pekanbaru - M. Rezki Ramadani; Mayarni Mayarni (UIR Press, 2021)
This research was conducted with the aim of knowing and explaining how community participation in tourism development and the inhibiting factors in carrying out tourism development in the Agrowisata Urban Village in Pekanbaru City. The theory used is the form of community participation according to Yadav in Totok Mardikanto which is divided into four types in the development and development process (1) participation in decision making (2) participation in implementation (3) participation in benefit (4) participation in evaluation. The type of research used is descriptive qualitative, data collection techniques obtained through observation, interviews, and documentation. The results of this study indicate that at the decision making stage, has involved the community in urban village deliberations activities to determine the policies for the activities carried out, the implementation carried out in the development has been going well with some of the activities carried out have received attention and brought tourists and the benefits of the results of the activities carried out have had an impact on development in the Agrowisata urban village area, but the benefits of tourism management have not been felt by all circles of society in the evaluation of tourist destinations developed in the management carried out it looks less competent, so that the development of agro-tourism destinations has not materialized. The inhibiting factors are human resources (HR), limited funds and the COVID-19 pandemic.